The Paradigm Of Inclusive Islamic Education - Supriyono; Mahmuhtarom; Ifada Retno Ekaningrum; Ghufron Hamzah (At Turots: Jurnal Pendidikan Islam, 2025)
Islam fundamentally promotes respect and the acceptance of diversity, asserting that all individuals—including persons with disabilities—possess inherent Human Dignity (ahsanu taqwim) and equal rights before God. Despite robust legal mandates in Indonesia, significant challenges persist within Islamic educational institutions (madrasahs). While the 1945 Constitution of the Republic of Indonesia guarantees the right to education for every citizen, and Government Regulation No. 13/2020 mandates that educational institutions provide Reasonable Accommodation for persons with disabilities, the practical implementation remains limited. Furthermore, although the Regulation of the Minister of Religious Affairs (PMA) No. 1/2024 has strengthened the framework for quality inclusive education in madrasahs, empirical data reveals a stark disparity: only 0.6% of registered Students with Special Needs in these institutions currently receive Reasonable Accommodation. This gap is exacerbated by systemic structural issues and prevailing social stigmas regarding institutional quality. This study seeks to reconstruct the paradigm of inclusive education within an Islamic context, advocating for a transition from mere regulatory compliance toward a profound spiritual and theological obligation. This research employs a qualitative approach utilizing library research. Data analysis was conducted through a systematic content analysis of primary Islamic texts, Indonesian legal frameworks, and empirical datasets retrieved from the Ministry of Religious Affairs' EMIS system. The study proposes a "Transformative Theo-Inclusive Paradigm" that synthesizes the Islamic principle of Human Dignity (Karamah Insaniyyah) with the pedagogical requirements of inclusive education. The findings indicate that while inclusive practices have been initiated in 1,070 madrasahs, quantitative progress remains inadequate due to a critical shortage of qualified Special Assistant Teachers (GPK) and limited supporting resources. This research emphasizes that the provision of Reasonable Accommodation is not merely a legal mandate but a manifestation of Islamic spirituality and religious practice (sunatullah). To bridge the divide between theological ideals and institutional realities, madrasahs must internalize inclusive values as a core religious mandate. This transformation necessitates systemic improvements in human resource competency and a fundamental shift in institutional perspectives to eliminate discrimination against Students with Special Needs.